2020
DOI: 10.1002/eji.202048544
|View full text |Cite
|
Sign up to set email alerts
|

Human T cells interacting with HNSCC‐derived mesenchymal stromal cells acquire tissue‐resident memory like properties

Abstract: Tissue-resident memory (Trm) cells are specialized components of both CD4+ and CD8+ T cell subsets that persist in peripheral nonlymphoid tissues following infections and provide fast response in case of a secondary invasion by the same pathogen. Trm cells express the surface markers CD69, CD103, and the immune checkpoint molecule PD-1. Trm cells develop not only in the context of infections but also in tumors, where they can provide a line of defense as suggested by the positive correlation between the freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…CD8 + T RM cells contributed to local immune protection in early-stage HGSOC tumors. To explain how CD8 + T RM cells form in early-stage HGSOC tumors, we checked the expression of survival factors, such as IL15 , IL17 , and NOTCH ligands, which are known to determine T RM cell formation and persistence ( 35–37 ). One of them, IL15 was expressed in HGSOC-derived malignant epithelial cells and induced the formation of CD8 + T RM cells and CD8 + T EX cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CD8 + T RM cells contributed to local immune protection in early-stage HGSOC tumors. To explain how CD8 + T RM cells form in early-stage HGSOC tumors, we checked the expression of survival factors, such as IL15 , IL17 , and NOTCH ligands, which are known to determine T RM cell formation and persistence ( 35–37 ). One of them, IL15 was expressed in HGSOC-derived malignant epithelial cells and induced the formation of CD8 + T RM cells and CD8 + T EX cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…From the analysis of our already published HNSCC-MSC transcriptome data [ 8 , 9 ] we observed that among the genes mostly upregulated by IFN-γ and TNF-α stimulation there were IDO1 and IL4I1 ( Figure 1 A). Upregulation of IDO1 was expected, given that its expression has already been described in HNSCC-MSC and its known dependency on IFN-γ signaling [ 7 ].…”
Section: Resultsmentioning
confidence: 98%
“…We have previously shown that MSC obtained from head–neck squamous cell carcinoma (HNSCC) inhibit T cell functions [ 7 ]. Moreover, we have shown that the transcriptional signature of HNSCC-MSC is strongly influenced by two cytokines commonly produced by anti-tumor T cells: IFN-γ and TNF-α [ 8 ]. In this study, we hypothesized that additional mechanism than IDO1 can be involved in the immunosuppressive activity of HNSCC-MSC.…”
Section: Introductionmentioning
confidence: 99%
“…Since the increase in PD-1 expression may be the result of T cell activation, PD-1 might remain upregulated in the context of a persistent antigen-specific immune stimulation. Furthermore, PD-1+ T cells include potentially tumor-specific T RM cells, exerting anti-neoplastic effects [ 43 ]. All these findings support the idea that PD-1 expression should not be merely considered as an exhaustion marker but rather a reflection of the antitumor reactivity, and suggest that patients with high expression of PD-1 on T cells could be potential candidates for anti-PD-1/PD-L1 blockade.…”
Section: Discussionmentioning
confidence: 99%